2014
DOI: 10.1016/j.arth.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Load Sharing and Ligament Strains in Balanced, Overstuffed and Understuffed UKA. A Validated Finite Element Analysis

Abstract: The aim of this study was to quantify the effects of understuffing and overstuffing UKA on bone stresses, load distribution and ligament strains. For that purpose, a numerical knee model of a cadaveric knee was developed and was validated against experimental measurements on that same knee. Good agreement was found among the numerical and experimental results. This study showed that, even if a medial UKA is well-aligned with normal soft tissue tension and with correct thickness of the tibia component, it induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 54 publications
6
97
0
Order By: Relevance
“…The comprehensive tibial component was then coupled to the corresponding femoral component considering an interaction friction coefficient of 0.1 to simulate the effect of synovial liquid. 8 A linear, elastic and isotropic material model was considered for all the materials used in this study [9][10][11] ; the material properties are detailed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensive tibial component was then coupled to the corresponding femoral component considering an interaction friction coefficient of 0.1 to simulate the effect of synovial liquid. 8 A linear, elastic and isotropic material model was considered for all the materials used in this study [9][10][11] ; the material properties are detailed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The boundary conditions of the squat movement, in terms of flexion-extension angle (up to 120 ) and axial force, were taken accordingly to previously experimental activities, 9,13 while the other degrees of freedom were kept free.…”
Section: Methodsmentioning
confidence: 99%
“…17 Innocenti et al studied the balanced load-sharing and ligament strains in overand under-stuffed UKA using an FE model with soft tissue structures. 18 To our knowledge, the joint line preservation, especially its biomechanical effects in UKA, have not been reported. In the present study, we develop validated FE model of UKA and evaluate the contact stress on the PE insert, tibial cartilage, and lateral meniscus, induced by post-operative change of the joint line.…”
mentioning
confidence: 88%
“…Kwon et al primarily included bony and soft tissue structures in an FE model for UKA and evaluated the effects of fixed‐ and mobile‐bearing UKA on the lateral meniscus under gait cycle loading conditions . Innocenti et al studied the balanced load‐sharing and ligament strains in over‐ and under‐stuffed UKA using an FE model with soft tissue structures …”
mentioning
confidence: 99%
“…However, the effect of adjusting tibial insert thickness on the biomechanical function of the knee, specifically the forces carried by the medial collateral ligament (MCL) and the anterior cruciate ligament (ACL), and the resulting kinematics through a range of flexion, are not well understood. A previous biomechanical study of UKA that integrated cadaveric testing and computational modeling reported the effect of adjusting tibial insert thickness on ligament strain and contact stress at full extension, but the interaction between tibiofemoral kinematics and ligament forces through a range of flexion was not described. Previous studies have reported that increasing the thickness of the polyethylene (PE) tibial insert lengthens the distance between the attachments of the superficial MCL during simulated activities in a cadaver model .…”
mentioning
confidence: 99%